Cinco de Mayo 1987- Parade and Fiesta (and Other Event) - Castellano, Alcario:::creator::::::::::::
Video of preparations for the Fiesta Carmela, Indoor Aztecs. Also included is a video of the 1987 Cinco de Mayo Parade (10:40) and the Fiesta Carmela, Indoor Aztecs (1:25:14).